Ethnic Origin of Catholicoses of Western Georgia - Abkhazia - Tkeshelashvili, Levan (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2022)
The Catholicate of Abkhazia has played a significant role in the religious and political landscape of Georgia for nearly a millennium. Its establishment dates back to the reign of the Kingdom of Abkhazia in Western Georgia during the 9th and 10th centuries. The Catholicate continued to exist throughout the era of the unified Georgian monarchy from the 11th to the 15th centuries, as well as during the formation of the Kingdom of Imereti from the 16th to the 18th centuries. Encompassing the entire of Western Georgia, the Catholicate of Abkhazeti held its seat in Bichvinta until 1565. However, due to the complex political circumstances arising from Ottoman invasions and migrations from the North Caucasus, King Bagrat III of Imereti (1510- 1565) and Catholicos Evdemon Chkhetidze (1557-1578) relocated the Catholic center from Bichvinta to Gelati in 1565. The Catholicate persisted until 1814. It is crucial to emphasize that a wealth of sources, documents, cultural and artistic works, including frescoes, manuscripts, legal monuments, and church inventory, as well as descriptive icons that have survived, unequivocally affirm the founding and existence of the Catholicate of Abkhazia within the Georgian reality. Furthermore, the Catholicoses themselves were of ethnic Georgian origin and conducted religious services in the Georgian language. The abundance of spiritual and cultural monuments created during the Catholicate›s existence was exclusively composed in Georgian, providing indisputable evidence of its formation and exist-ence within the Georgian context. Any attempt by contemporary «researchers» or ill-founded publications to challenge this historical fact will undoubtedly fail. In the future, it is imperative to produce a dedicated monograph on the Catholicos of Abkhazia, available in multiple languages, to provide an accurate account of the true history of the Catholicos of Abkhazia (Western Georgia) and disseminate this knowledge to a wider audience.